Submicrosecond Q-Switching Er-Doped All-Fiber Ring Laser Based on Black Phosphorus - Yao Cai; Yanliang He; Xiaoke Zhang; Rui Jiang; Chenliang Su; Ying Li (Advances in Condensed Matter Physics)
Black phosphorus (BP), a new two-dimensional (2D) material, has been deeply developed for extensive applications in electronics and optoelectronics due to its similar physical structure to graphene and thickness dependent direct band gap. Here, we demonstrated a submicrosecond passive Q-switching Er-doped fiber laser with BP as saturable absorber (SA). The BP saturable absorber was fabricated by mechanical exfoliation method. By taking full advantage of the ultrafast relaxation time of BP-SA and careful design of compact ring cavity, we obtained stable Q-switching pulses output with a shortest duration as narrow as 742 ns. With increasing the pump power, the pulse repetition rate accreted gradually almost linearly from 9.78 to 61.25 kHz, and the pulse duration declined rapidly at lower pump power regime and retained approximate stationary at higher pump power regime from 3.05 to 0.742 μs. The experimental results indicate that BP-SA can be an effective SA for nanosecond Q-switching pulse generation.